2018
DOI: 10.3390/ijerph15040663
|View full text |Cite
|
Sign up to set email alerts
|

The Elderly Perceived Meanings and Values of Virtual Reality Leisure Activities: A Means-End Chain Approach

Abstract: This study uses means-end chain (MEC) techniques to examine the awareness, decision-making procedure, and personal values of the elderly with regard to virtual reality leisure activities. The results of the study show that elderly respondents value virtual reality leisure activities that are fun, safe, and easy. In terms of outcome benefits, elderly respondents value feeling physically and mentally healthy, firsthand experience, and satisfied curiosity. In value terms, elderly respondents hope that their chose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 46 publications
1
34
0
4
Order By: Relevance
“…There are still lack of x-reality technology used in Indonesia destination therefore, further research can be carried out experimental research through on lab or web based VR [8,25]. In addition, research on the influence of virtual tourism can be carried out for traumascape, disability and elderly [6,34,35].…”
Section: Discussionmentioning
confidence: 99%
“…There are still lack of x-reality technology used in Indonesia destination therefore, further research can be carried out experimental research through on lab or web based VR [8,25]. In addition, research on the influence of virtual tourism can be carried out for traumascape, disability and elderly [6,34,35].…”
Section: Discussionmentioning
confidence: 99%
“…A study conducted in Taiwan in 2018 confirmed the above issues. Moreover, Lin, Jeng, and Yeh (2018) also found that elderly respondents appreciate the virtual reality leisure activities that are fun, safe, and easy. For the outcome benefits, elderly respondents highly value a sense of physical and mental well-being, self-directed learning experience, and satisfying curiosity.…”
Section: An Overview Of the Nursing Home Servicementioning
confidence: 96%
“…At the same time, there is an extensive discussion (in medical, social, and ethical fields) on the extent to which robots and VR can replace man in the treatment, rehabilitation, and taking care of ill, disabled, and old people [22,30]. In the opinion of the authors of this paper, the answer is obvious: the participation of new technologies will grow year by year.…”
Section: Future Research Directionsmentioning
confidence: 96%